Comprehensive Analysis of the Built Environment through the Introduction of Induced Impacts via Transportation: Detailed Case Study for the Urban Region of Munich, Germany. Issue 1 (January 2015) - Anderson, John E.; Wulfhorst, Gebhard; Lang, Werner
The built environment, accounting for the building and transportation sectors, is the dominant source of environmental impacts. While significant research has assessed environmental impacts in the built environment, existing research is strongly separated by the scale of analysis: individual buildings or the urban scale. However, assessing buildings as isolated objects ignores their urban context, while concentrating on urban-scale projects does not represent the actual scale of construction: growth within existing cities. As such, environmental impacts resulting from the interplay of individual buildings and their urban context, induced impacts, have yet to be determined. This paper presents a new methodology for capturing induced impacts in the built environment. The new methodology was applied to the urban region of Munich, Germany, at three geographical resolutions (traffic cell, city neighborhood, and district) to illustrate the significance of induced impacts. The research contributes to the literature through the integration of the assessment of the transportation infrastructure in addition to the traditional focus on operational impacts. Transportation embodied impacts were found to account for approximately 25% of greenhouse gas emissions. Furthermore, transportation impacts (embodied and operational) were summarized at three locations: city center, city periphery, and rural. Consequently, the work has identified a missing impact category, expanded the assessment methodology, and provided quantitative analysis for holistic evaluation of the built environment. The inclusion of induced impacts allows for innovative policies to achieve environmental goals within the built environment.